Effect of hydrothermal treatmenton Cr-SiO2 mesoporous materials - Cuesta Zapata, Pablo Martín (2013)
Cr/SiO2 (MCM-41) materials were prepared by the sol–gel method by hydrolysis of tetraethylortosilicate (TEOS) using cetyltrimethylammonium bromide (CTAB) as a template. The effect of hydrothermal treatment between 120–220 °C on the structural properties was studied. Well ordered Cr/MCM-41 with a very narrow pore size distribution was obtained after hydrothermal treatment from RT to 150 °C. Materials synthesized at higher temperatures (200 or 220 °C) showed the collapse of the ordered mesoestructure to give mesoporous Cr/SiO2 with an open surface. Superficial Cr3+/Cr6+ ratio was determined by XPS over materials hydrothermically synthesized at different temperatures, and calcined in air at 300 °C. The hydrothermal treatment improved the chromium to silica interaction, promoting a higher resistance to form Chromium (VI) sites. The chromium (III) ions incorporated to the silica structure developed acid sites responsible for the 2-PrOH dehydration.